Specifics of Receiving Evidence in the Criminal Procedure of the Republic of Kazakhstan - BEKISHEV, Askhat K.; UMIRZAKOVA, Zhansaya; SALAMATOVNAIBRAEVA, Alua; KUTIBAEVA, Elizaveta; SALAMATOVICHIBRAYEV, Nurlan (Journal of Advanced Research in Law and Economics, 2019)
The research discusses the specifics of receiving evidence in the criminal procedure of the Republic of Kazakhstan. The authors of the article analyze the criminal procedure legislation of the Republic of Kazakhstan related to receiving evidence during the pre-trial investigation of a criminal case. Having conducted a scientific analysis, they have determined the main features of receiving evidence in the criminal procedure. The study has revealed the main types of evidence and provided their characteristics. The authors have considered the procedural order of investigative actions that are based on receiving evidence (interrogation, face-to-face confrontation, presentation for identification, evidence verification and clarification at the scene, investigative experiment). According to the study results, the authors have concluded that the effectiveness of receiving evidence during the pre-trial investigation of a criminal case consists of many objective and subjective factors but the main ones are strict adherence to the corresponding law and professional skills of the official investigating the crime in question.